2016
DOI: 10.1017/ice.2016.32
|View full text |Cite
|
Sign up to set email alerts
|

A Central Line Care Maintenance Bundle for the Prevention of Central Line–Associated Bloodstream Infection in Non–Intensive Care Unit Settings

Abstract: Objective To evaluate a central line care maintenance bundle to reduce central line-associated bloodstream infection (CLABSI) in non-ICU settings. Design Before-after trial with 12 month follow-up period. Setting 1250-bed teaching hospital. Participants Patients with central lines on eight general medicine wards. Four wards received the intervention and four served as controls. Intervention A multifaceted catheter care maintenance bundle consisting of educational programs for nurses, update of hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 33 publications
(41 reference statements)
4
27
0
3
Order By: Relevance
“…The educational course in this study was successful in expanding nurses’ knowledge of CVC-RI prevention guidelines. This finding is consistent with those of many other studies that indicated the benefits of such courses in the improvement of nurses’ knowledge (Hina and McDowell, 2017; O’Neil et al., 2016). It is also congruent with the recommendations of the Centers for Disease Control and Prevention and the American Thoracic Society for continuing education and training as a basic element in CVC-RI prevention (Labeau et al., 2009; O'Neil et al., 2016).…”
Section: Discussionsupporting
confidence: 93%
“…The educational course in this study was successful in expanding nurses’ knowledge of CVC-RI prevention guidelines. This finding is consistent with those of many other studies that indicated the benefits of such courses in the improvement of nurses’ knowledge (Hina and McDowell, 2017; O’Neil et al., 2016). It is also congruent with the recommendations of the Centers for Disease Control and Prevention and the American Thoracic Society for continuing education and training as a basic element in CVC-RI prevention (Labeau et al., 2009; O'Neil et al., 2016).…”
Section: Discussionsupporting
confidence: 93%
“…Our positive CLABSI incidence rate was 2.0% (1.8 per 1000 device days); a rate that is in line with reported rates from other non-ICU cohorts 18 but higher than in centres where there has been a focus on reaching a zero CLABSI rate. 19,20 While the trial was not designed to test for differences, it provides some preliminary data on the efficacy of the two products.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 90%
“…In the present study, there was a greater proportion of Gram-negative than Gram-positive microorganisms, unlike most studies conducted in North America that show a higher frequency of Gram-positivity in CVC-BSIs [3032]. However, it corroborates with other studies previously published in several countries and regions [3235].…”
Section: Discussionsupporting
confidence: 89%